P5-S3.03 Individual tracking among high risk groups for STI management in India: an analysis of 400 000 high risk groups followed from 2004 to 2009. (10th July 2011) - Gurung, A; Narayanan, P; Mugundu, P; Ranjan, M; Kumar, R; Prabhakar, P; Das, A
Abstract : Background: Avahan, the India AIDS Initiative of the Bill & Melinda Gates Foundation implemented a large HIV prevention program across six high HIV prevalence states among high risk groups (HRG) consisting of female sex workers (FSW), high risk men who have sex with men (HR-MSM), transgender (TG) and injecting drug users (IDU) in India. Methods: The Avahan monitoring system included individual tracking data pertaining to registration, outreach and clinical services among HRG. All clinic visits were recorded using unique identification numbers, and visits by each clinic attendee were tracked from January 2004 to December 2009. Each clinic visit was recorded using a pre-defined clinical encounter form (CEF). Results: A total of 439 000 individuals (including 331 616 FSW, 10 280 IDU, 82 246 H- MSM, and 7330 TG) visited the clinics with a total of 2 716 391 visits. Individuals made an average of 6.2 visits to the clinics during the study period. The number of visits per person increased annually from 1.2 in 2005 to 8.3 in 2009. The proportion of attendees visiting clinics more than four times a year increased from 4% in 2005 to 26% in 2009 (p<0.001). The proportion of syndromes diagnosed among FSW decreased from 39% in 2005 to 11% in 2009 (p<0.001) while the proportion of syndromes diagnosed among HR-MSM decreased from 11.6% to 3.5 % (p<0.001). The proportion of attendees seeking regular STI check-ups increased from 12% to 48% (p<0.001). The proportion of HRG accessing clinics within 2 days of the onset of STI-related symptoms and acceptability of speculum and proctoscope examination increased significantly (p<0.001) see Abstract P5-S3.03 figure 1 . Conclusions: The project demonstrated that acceptable and accessible services with marginalised and often difficult-to-reach populations can be brought to a very large scale using standardised approaches. The paper presents the utilisation of these services, improved health seeking behaviour and reduced STI syndromes among the HRG.